Expression of P16 in Surface Epithelial Ovarian Neoplasm (Journal of Dhaka Medical College, 2023)
Background: Epithelial ovarian carcinoma is the major subtype of ovarian cancer, one of the most lethal gynaecological malignancies. Due to some difficulties in early detection, patients are usually diagnosed at advanced stages, and overall survival is poor. P16 is a tumour suppressor gene that regulates the cell cycle by inhibiting S phase. Studying experssion of this immunohistochemical marker will help to diagnose and predictrognosis of ovarian epithelial tumours. The study’s objective was to evaluate the expression of p16 in surface epithelial ovarian neoplasm and its association with histo-pathological grading.Methodology: This cross-sectional study was carried out at the Department of Pathology, Sir Salimullah Medical College, Dhaka. A total of 46 patients diagnosed histo-pathologically as surface epithelial ovarian neoplasm were included in the study. In addition, P16 immuno-staining, as well as some demographic and clinical data, were also evaluated.Result: The mean age of the patient was 48.04 ± 12.182SD years. The most common histologic subtype was serious, followed by the mucinous type. P16 was positive in 40 (86.96%) cases. A statistically significant difference in p16 expression was observed between tumour types and between tumour grades. Up-regulation of p16 expression was observed in malignant tumours more than in benign tumours. P16 expression was increased with increased grading of the malignant tumours.Conclusion: P16 expression is associated with histo-pathological grading in ovarian epithelial carcinoma.J Dhaka Med Coll. 2022; 31(1) : 71-76